From apartheid to democracy : a blueprint for peace in Israel-Palestine - Omer-Man, Michael Schaeffer; Whitson, Sarah Leah (University of California Press, 2025)
"A decisive break from the failed Oslo Accords and an innovative plan to create the foundations for peace and self-determination in Israel-Palestine. For more than three decades, the illusion of a two-state solution under the auspices of the Oslo Accords has allowed Israel to maintain a one-state reality of permanent occupation and apartheid. Michael Schaeffer Omer-Man and Sarah Leah Whitson challenge this approach, presenting a road map to end these crimes and create a rights-respecting regime for everyone now living under Israeli control. Only once basic safety and legal equality are assured can Jewish Israelis and Palestinians determine their futures-in one, two, or more states if they choose-through an inclusive, democratic process. Breaking with the failures of the past, the plan presented here makes clear that ongoing violations of basic human rights must be ended before issues of governance can be equitably addressed. Clear-eyed yet hopeful, Omer-Man and Whitson offer proof of concept that democracy and equality are indeed attainable-and call on the international community to create the conditions required for them to flourish"-- Provided by publisher.